Variations in the archaeal community in wetlands soils under various hydrologic conditions in the Yellow River Estuary - Zhao, Qingqing; Jia, Jia; Song, Fanyong; Li, Tianyuan; Zhang, Wen; Huang, Yujie (Frontiers in Marine Science, 2025)
Unraveling the relationships between archaea and factors influencing their diversity and distribution is a critical issue in marine ecosystems. Here, the archaeal diversity and community structure in 0 - 20 cm soils from freshwater influenced wetlands (FIW), flooding freshwater and underground seawater influenced wetlands (MIW) and seawater influenced wetlands (SIW) in the Yellow River Nature Reserve were examined utilizing high-throughput sequencing of 16S rRNA gene sequencing. Based on the comparison of the alpha diversity indices, the abundance and diversity of the archaeal community in wetlands with varying hydrologic conditions did not significantly change (p > 0.05), with Thaumarchaeota and Marine_Group_I as the predominant archaeal phylum and class in all the three sampled sites, respectively. Thaumarchaeota, Woesearchaeota and Euryarchaeota constituted more than 90% of the total soil archaeal community in all wetlands. However, beta diversity indices revealed that significantly different distribution patterns of archaea were found among the three wetlands (p < 0.05). And the archaeal community structure in different wetlands varied as the hydrologic conditions changed. Less discriminated archaeal taxa were found in MIW (1 taxon) than in FIW (24 taxa) and SIW (18 taxa). Furthermore, statistical analysis confirmed that the difference in soil salinity caused by different hydrologic conditions was the major driver of archaeal community structure. Overall, this study highlights the role of hydrologic conditions in structuring the soil archaeal community in coastal wetlands.